Risk neutral and risk averse Stochastic Dual Dynamic Programming method - Shapiro, Alexander; Tekaya, Wajdi; da Costa, Joari Paulo; Soares, Murilo Pereira (European journal of operational research, 2013)
► Generic description of the Stochastic Dual Dynamic Programming (SDDP) method is given. ► Case studies related to operation planning of the Brazilian interconnected power system are presented. ► Risk averse approaches to multistage stochastic programming adjusted to the SDDP method are developed. ► General methodology is tested in extensive numerical experiments. ► Risk neutral and risk averse SDDP method could be a reasonable approach if the number of state variables is small. In this paper we discuss risk neutral and risk averse approaches to multistage (linear) stochastic programming problems based on the Stochastic Dual Dynamic Programming (SDDP) method. We give a general description of the algorithm and present computational studies related to planning of the Brazilian interconnected power system.